2019
DOI: 10.20473/jvhs.v3.i2.2019.53-58
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity Test Using Amla Fruit (Phyllanthus Emblica L) Extract in Alloxan-Induced Balb/C Mice

Abstract: Background: The content of secondary metabolites in amla (phyllanthus emblica L.) such as flavonoids and phenols have the potential as an antioxidant. One of the benefits of antioxidants is to prevent degenerative diseases, such as diabetes mellitus. Purpose: This research to determine activity of amla fruit extract in reducing blood glucose levels at balb/c mice induced with alloxan. Methods. This research method uses a pre and posttest-controlled group design with 35 balb/c mice divided into five treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The process of taking blood was carried out on the tail of each mouse to check blood glucose levels. After that, mice with blood glucose levels above 200 mg/dl were used in this study because mice were considered to have hyperglycemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…The process of taking blood was carried out on the tail of each mouse to check blood glucose levels. After that, mice with blood glucose levels above 200 mg/dl were used in this study because mice were considered to have hyperglycemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that alloxan increased the concentration of cytosolic free calcium in pancreatic β cells as a result of several processes, including increased influx of calcium from the extracellular fluid, intracellular mobilization, and reduced calcium loss in the cytoplasm. The ability of alloxan to cause diabetes also depends on the induction pathway, dose, compounds, experimental animals and nutritional status (Cahyaningrum et al, 2019).…”
Section: Antidiabetic Test Using Aloksan Induction Methodsmentioning
confidence: 99%
“…Antioksidan alami dapat diperoleh dari tanaman malaka yang memiliki nama botani Phyllanthus emblica L. Kandungan flavonoid pada buah malaka dijadikan sebagai sumber antioksidan alami yang mampu mencegah penyakit yang umum muncul diusia tua yang diakibatkan penurunan fungsi sel dan efektif meningkatkan imunitas tubuh (Cahyaningrum et al, 2019;Gul et al, 2022;Huang et al, 2023;Kumar et al, 2022). Keseluruhan bagian tumbuhan malaka ini seperti biji, akar, ranting, bunga, daun dan buah diolah secara tradisional di negara India sebagai pengobatan yang kaya akan khasiat (Ahmad et al, 2021;Saini et al, 2022).…”
Section: Pendahuluanunclassified